An Analysis of Students' Ability in Distinguishing Lexical and Structural Ambiguity in English Sentences at Second Grade of SMA 1 Labuapi in the Academic Year 2016-2017 - Irwandi Irwandi (Muhammadiyah University of Mataram, 2017)
Ambiguity is the property of having two or more distinct meanings or interpretations. Sometimes we found many ambiguities sentences when we are reading or listen to the English sentences. A word or sentence is ambiguous if it can be interpreted in more than one way. The problem stated in this study is: How is the students’ ability in distinguishing lexical and structural ambiguity in English sentences? The purpose of this study is to investigate the students’ ability in distinguishing lexical and structural ambiguity in English sentences at second grade of SMAN 1 Labuapi in academic year 2016/2017. This study used a descriptive qualitative approach. The writer used purposive sampling for taking the sample, namely class IPA 2 which consists of 22 students. The data were collected by a gap-filling test for lexical ambiguity word class of noun and label for structural ambiguity. The results of the research demonstrate that the students of SMAN 1 Labuapi were categorized into a very poor with the average score was 4.450. The writer illustrates the analysis result in the percentage of all test’s items in simple sentences, there were 890 ambiguous words and phrase. Lexical ambiguity involves noun (150) and structural ambiguity involve noun phrase (30). Finally, based on the research findings, the writer concluded that more than a half of students at the second grade of SMAN 1 Labuapi had very poor abilities in distinguishing lexical and structural ambiguity in English sentences.